Curriculum Design and Scholarship for New Educators: A Professional Development Workshop for Medical Students - Elisabeth F.M. Schlegel; Jeffrey B. Bird; Christopher M. Burns; Michael Cassara; Jessica O'Neil; Yun Weisholtz; Tao T. Le (Association of American Medical Colleges, 2021)
Introduction Medical students' professional development includes their role as educators. Despite greater opportunities to join medical education curriculum development, medical students' engagement in these activities remains limited. A recent national study on student leadership in curricular change revealed a formal lack of leadership and training in medical education as significant barriers. Medical students' unawareness of how to disseminate curricula as educational scholarship and its value to their careers also restricts the fullness of their formation as educators. Methods We designed a 3-hour, interactive, project-focused conference workshop for medical students without prior knowledge in curriculum development. Of participants, 64 worked in 10 groups creating medical curricula using Kern's six-step approach in student-facilitated breakout sessions. Completed group projects were presented, including brief action plans for transforming their work into scholarship. The workshop was evaluated using a mixed-methods approach. Results Of survey respondents, 44 mostly medical students, faculty, and administrators from different institutions rated the workshop as a very positive experience, and the pacing of the breakout groups as effective. A notable increase in self-reported mastery, as measured by learning objectives aligned with Kern's six-step model, was recorded from student respondents as compared to faculty. A sense of readiness to participate in curricular decisions either at the home institution or in individual career paths was evident from narrative comments. Discussion Our workshop provided medical students with a foundation in curriculum development and educational scholarship. Session design provided flexibility in the pace of breakout sessions and allowed in-depth discussion of educational topics.